Vivência e lembrança na voz poética de Juca da Angélica - Paula, Andréa Cristina de (2018)
This work aims to analyze some poems by José Joaquim de Sousa, popularly known as Juca da Angélica, starting from the poetic repertoire constituent of the book Meu canto é saudade (2001 and 2011), which contains part of the lyrical production of the author. Our purpose is to reflect on the representation that this poet of oral literature makes of his life experiences, under the mnemonic look of an individual, whose identity is characterized by its intimate relationship with the space in which it inhabits (the farm) and daily activities inherent to the place where he was born and raised. As he lacked close contact with writing, Juca's literary repertoire is basically composed of his memories, in a kind of "lyrical autobiography" (NEPOMUCENO, 2001, page 13), in which "precise information about the society of Minas Gerais, the family, the organization of the community, values, ethics, a register of life, finally "(NEPOMUCENO, 2001, 19). In this sense, it is an oral poetics based on the poet's recollections of past events - events related to the actions of his daily life, which are recorded in his poetry in which "the story, a bundle of stories to which are added accidents, disappointments, adventures, hopes, homesickness, is engendered by the exercise of the activity of the eye "(FERNANDES, 2007). It is, therefore, the look that Juca throws to the activities that permeate the rural society in which it is inserted that interests to this study. A look that constitutes its identity, formed by the memory of life / time, in which is the symbolic dichotomy between the young and the old; the memory of space, in which are located the memories of the poet as to his routine of work in the rural scope; and the memory of the rites, formed by festive-religious practices that also belong to the social scene of which the author is a part. Such a study has arisen in the light of memory scholars such as Ecléa Bosi (1994), Agamben (2009), Benjamim (1994), Gagnebin (2014), among other theorists of the area; (2005 and 2007) and Frederico Fernandes (2003 and 2007), as well as authors dedicated to the publication of texts that deal with the popular culture of the interior of Minas Gerais, such as Maria Clara Machado (2006), as well as on studies about poetry, as defined by Octávio Paz (1982). Finally, it is necessary to delimit the critical-methodological path adopted in the development of this research, namely: a reflexive analysis of the poetics of Juca da Angélica, in order to transcend a merely "descriptivist" or "Impressionist" posture, balance that takes into account the particularities of the work, respecting the socio-historical context in which it is inserted. Therefore, this study assumes the commitment to analyze the voice (individual and collective) of Juca da Angélica, focusing on the look he throws into his life and his relationship with the Other, reconstituting, through memory, the " being lived in being remembered ", in an activity in which its most varied facets are revealed and in which the present time refers to the search for a “lost time” (PROUST, 2004) that only by poetic memory can be rescued.